Understanding Extension for School-Based Agricultural Education #2: Utilizing Extension Services in School-Based Agricultural Education - Debra Barry; John Diaz; Alyssa Shepherd; Jennifer Patton; Stephen Gran (EDIS)
The services that Extension offers can supplement lesson plans in the classroom, can help to provide training and support for educators, and can help to build the toolbox of both first-year educators and the veteran educators that want to expand on their current lesson plans and resources. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication helps to describe how UF/IFAS Extension can be utilized in agricultural education. Written by Debra Barry, John Diaz, Alyssa Shepherd, Jennifer Patton, and Stephen Gran. (The title of this article was adjusted on October 14, 2020, to match other entries in the series.) https://edis.ifas.ufl.edu/wc367